Curriculum Analysis of Permai Plus School at Pluit’s Elementary Chinese Course - Yetty Yetty (Humaniora, 2010)
In Indonesia, in addition to english mandarin also become a very common thing. Many companies employ one of the conditions of staff must be fluent in speaking Chinese, reading and writing Chinese characters. Therefore, the majority of schools in Indonesia have set up Chinese language courses, in order to give Chinese language’s basic foundation to their students. In Pluit, courses of Chinese language schools are mostly private, three-language schools and international schools (not including international schools in the U.S. system). Through the six factors of curriculum (Teachers, facilities, scores, textbooks, curricula, and social participation ), the writer wants to analyze Permai Plus school curriculum Chinese course situation.